2022
DOI: 10.3389/fdgth.2022.833006
|View full text |Cite
|
Sign up to set email alerts
|

Peer Facilitators as Core Co-developers of an Online Peer Encouragement Network (OPEN2chat) for Austrian Adolescents

Abstract: Adolescence is a crucial developmental time, and it is essential to ensure stable mental health during the transition to adulthood. Peer-to-peer networks seem to be a promising tool to support adolescents during that time. While co-development often concentrates on the end-user, this paper focuses on the peer facilitators of an online peer encouragement network (OPEN2chat), where adolescents can chat with peer facilitators about their problems. We conducted 3 group discussions with 18 peer facilitators after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…Nevertheless, several factors must be considered: Legal frameworks might need to be adapted for different countries [ 8 ], and therapists might need support when transitioning to online interventions [ 8 , 27 ]. Regarding the development of such interventions, studies have shown positive effects by including peer groups in the development process [ 34 , 36 ] and using peers as advisors [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several factors must be considered: Legal frameworks might need to be adapted for different countries [ 8 ], and therapists might need support when transitioning to online interventions [ 8 , 27 ]. Regarding the development of such interventions, studies have shown positive effects by including peer groups in the development process [ 34 , 36 ] and using peers as advisors [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several factors must be considered: Legal frameworks might need to be adapted for different countries [8], and therapists might need support when transitioning to online interventions [8,27]. Regarding the development of such interventions, studies have shown positive effects by including peer groups in the development process [34,36] and using peers as advisors [35,37]. However, using digital media and smartphones in and of themselves might pose risk factors for children and adolescents: An increase in cyber victimization through media use has been found [57], and young people are more at risk for addictive behavior in general [7].…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Verunsicherung, Einsamkeit, Lockdown und Distance Learning (Berger et al, 2021;Huber und Helm, 2020): Bereits vor der Pandemie litten mindestens 20 % der österreichischen Jugendlichen an psychischen Problemen (Wagner et al, 2017) So konnte mit dem Projekt open2chat durch Forschung schon vor der Pandemie der Bedarf eines niederschwelligen Behandlungsangebots als asynchron sowie synchron nutzbares Chat-Programm identifiziert und die Entwicklung bereits 2019 begonnen werden (Mägde et al, 2020). Bei der Entwicklung wurden Jugendlichen von Anfang an mit involviert (Mittmann, Schmalwieser, Diendorfer, Schrank, & Boeckle, 2022). Dadurch wurden und werden die Web-Applikation stetig an die Bedürfnisse der Jugendlichen angepasst (Mittmann et al, 2022) (Jesser, Schmalwieser, Diendorfer et al, 2021) sowie theoretische Zugänge und praktische Lösungen miteinander verbunden (Schmalwieser, Jesser, Mädge, Schrank, & Boeckle, 2022).…”
Section: Caring Als Gemeinsames Unterstützungsnetzwerkunclassified
“…Bei der Entwicklung wurden Jugendlichen von Anfang an mit involviert (Mittmann, Schmalwieser, Diendorfer, Schrank, & Boeckle, 2022). Dadurch wurden und werden die Web-Applikation stetig an die Bedürfnisse der Jugendlichen angepasst (Mittmann et al, 2022) (Jesser, Schmalwieser, Diendorfer et al, 2021) sowie theoretische Zugänge und praktische Lösungen miteinander verbunden (Schmalwieser, Jesser, Mädge, Schrank, & Boeckle, 2022).…”
Section: Caring Als Gemeinsames Unterstützungsnetzwerkunclassified